2008
DOI: 10.1111/j.1475-097x.2008.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal respiratory‐related evoked potentials in untreated awake patients with severe obstructive sleep apnoea syndrome

Abstract: The cortical processing of airway occlusion-related afferents seems abnormal in untreated patients with severe obstructive sleep apnoea syndrome. This could be either a severity marker and/or an aggravating factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…or not evaluated at all. Excluding the four pediatric studies: in one report patients were included that were likely to be affected by OSAS but the disturbed breathing was not recorded (Wong et al , 2006 ), three did not clearly specify the degree of OSAS (Walsleben et al , 1989 ;Rumbach et al , 1991 ), three included mild OSAS (one of which together with severe OSAS) (Gora et al , 2002 ;Zhang et al , 2002 ;Afi fi et al , 2003 ), eight papers included rather severe OSAS patients (Kotterba et al , 1998 ;Delgado Rodrigues et al , 2006 ;Gosselin et al , 2006a,b ;Sforza and Haba -Rubio, 2006 ;Donzel -Raynaud et al, 2009 ;Neu et al , 2011 ) and fi ve included individuals with different degrees of severity of OSAS, ranging from mild to severe Sangal , 1995, 1997a,b,c ;Inoue et al , 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…or not evaluated at all. Excluding the four pediatric studies: in one report patients were included that were likely to be affected by OSAS but the disturbed breathing was not recorded (Wong et al , 2006 ), three did not clearly specify the degree of OSAS (Walsleben et al , 1989 ;Rumbach et al , 1991 ), three included mild OSAS (one of which together with severe OSAS) (Gora et al , 2002 ;Zhang et al , 2002 ;Afi fi et al , 2003 ), eight papers included rather severe OSAS patients (Kotterba et al , 1998 ;Delgado Rodrigues et al , 2006 ;Gosselin et al , 2006a,b ;Sforza and Haba -Rubio, 2006 ;Donzel -Raynaud et al, 2009 ;Neu et al , 2011 ) and fi ve included individuals with different degrees of severity of OSAS, ranging from mild to severe Sangal , 1995, 1997a,b,c ;Inoue et al , 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Gora et al ( 2002) and Afi fi et al (2003) found an altered response to the respiratory occlusion stimulus in adults with OSAS during non-REM sleep stage 2, that they indicated as being ' blunted ' . In contrast, delayed N1, P2, N2 components without alterations in amplitude were found during wakefulness (Donzel -Raynaud et al, 2009 ).…”
Section: A Short Essay On Respiratory-related Evoked Potentialsmentioning
confidence: 93%
See 1 more Smart Citation
“…Consistent with impaired sensory transmission to respiratory stimuli, two studies revealed a reduction in the amplitude but not the latency of the early RREP components to brief negative pressures during inspiration (Akay et al, 2003) and expiration (Grippo et al, 2011). However, other studies have shown no difference in P1 amplitude or latency (reflecting the arrival of the sensory information to the cortex) of the RREP to inspiratory occlusions and negative pressures in OSA patients (Gora et al, 2002; Afifi et al, 2003; Donzel-Raynaud et al, 2009; Eckert et al, 2011). During sleep, P1 does not appear to be different between OSA patients and controls (Gora et al, 2002; Afifi et al, 2003).…”
Section: Evidence For Upper Airway Afferent Changesmentioning
confidence: 95%
“…The respiratory-related evoked potentials (RREPs) during wakefulness in OSA revealed a reduction in the amplitude but not the latency of the early RREP components [44,47] reflecting sensory processing is reduced in the OSA patients [48]. Other studies revealed no changes [49][50][51].…”
Section: Sleep Apnea -Recent Updatesmentioning
confidence: 99%